Energy transfer and trapping in photosystem I reaction centers from cyanobacteria. - DiMagno, L (1995)
A mutant strain of the cyanobacterium Synechocystis 6803, TolE4B, was constructed by genetic deletion of the protein that links phycobilisomes to thylakoid membranes and of the CP43 and CP47 proteins of photosystem II (PSII), leaving the photosystem I (PSI) center as the sole chromophore in the photosynthetic membranes. Both intact membrane and detergent-isolated samples of PSI were characterized by time-resolved and steady-state fluorescence methods. A decay component of approximately 25 ps dominates (99% of the amplitude) the fluorescence of the membrane sample. This result indicates that an intermediate lifetime is not associated with the intact membrane preparation and the charge separation in PSI is irreversible. The decay time of the detergent-isolated sample is similar. The 600-nm excited steady-state fluorescence spectrum displays a red fluorescence peak at approximately 703 nm at room temperature. The 450-nm excited steady-state fluorescence spectrum is dominated by a single peak around 700 nm without 680-nm "bulk" fluorescence. The experimental results were compared with several computer simulations. Assuming an antenna size of 130 chlorophyll molecules, an apparent charge separation time of approximately 1 ps is estimated. Alternatively, the kinetics could be modeled on the basis of a two-domain antenna for PSI, consistent with the available structural data, each containing approximately 65 chlorophyll a molecules. If excitation can migrate freely within each domain and communication between domains occurs only close to the reaction center, a charge separation time of 3-4 ps is obtained instead.